2012
DOI: 10.1097/moh.0b013e328353c684
|View full text |Cite
|
Sign up to set email alerts
|

Role of SALL4 in hematopoiesis

Abstract: The emerging knowledge about how SALL4 regulates HSC behavior may be used in the near future to develop advanced cell therapies, for example, through large-scale stem cell expansion ex vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Furthermore, knockdown of SALL4 significantly reduces the efficiency of induced pluripotent stem cell generation [31]. SALL4 is also expressed in hematopoietic stem cells and leukemia cells, where it regulates their maintenance [14,32]. SALL4 is known to encode two isoforms (SALL4A and SALL4B), and a recent study suggested the important role of SALL4B on maintaining the stemness of embryonic stem cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knockdown of SALL4 significantly reduces the efficiency of induced pluripotent stem cell generation [31]. SALL4 is also expressed in hematopoietic stem cells and leukemia cells, where it regulates their maintenance [14,32]. SALL4 is known to encode two isoforms (SALL4A and SALL4B), and a recent study suggested the important role of SALL4B on maintaining the stemness of embryonic stem cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of SALL4 gene have been detected in patients with several developmental disorders, and these mutations either occur in the transactivation domain or cause premature translational termination. 12,41,42 To date, no mutations have been reported that reside in the nuclear localization domain. It is likely that this type of mutations may severely disrupt the function of SALL4, thus leading to embryonic lethality.…”
Section: 39mentioning
confidence: 99%
“…10,11 Mutations of SALL4 gene are associated with several developmental syndromes, including Okihiro syndrome, acro-renalocular syndrome, and IVIC syndrome. 12 Aberrant expression of SALL4 is associated with development of various types of malignancies. [13][14][15] It is proposed that SALL4 may have a diagnostic or prognostic value.…”
Section: Introducitonmentioning
confidence: 99%
“…However, the distribution of Sall4 after birth is restricted to the adult stem/stemlike cells, preferentially in bone marrow and gonadal tissues (Sweetman and Münsterberg, 2006). Sall4 is enriched in ESCs and is critical for maintaining the stemness of ESCs (Kohlhase et al, 2002;Koshiba-Takeuchi et al, 2006;Sweetman and Münsterberg, 2006;Yuri et al, 2009;Yang et al, 2012). Recent studies have highlighted that Sall4 could positively and negatively regulate gene expression through its interaction with the epigenetic machineries, such as M ouse embryonic stem cells (ESCs) are genetically more stable than somatic cells, thereby preventing the passage of genomic abnormalities to their derivatives including germ cells.…”
Section: Introductionmentioning
confidence: 99%